Poesies d'anacréon - Capperonnier, Jean, 1716-1775.
One volume (338 pages) containing translations of Greek poetry, detailed and scholarly explanations of translation and text, and comparison or criticism of previously published translations.
Translator, classicist, and scholar.
Collection material in French.
Keywords: Literature; Poetry; Classicists; Scholars; Translators